2017
DOI: 10.1111/myc.12729
|View full text |Cite
|
Sign up to set email alerts
|

Epidural abscess caused by Schizophyllum commune: A rare case of rhinogenic cranial complication by a filamentous basidiomycete

Abstract: Central nervous system (CNS) infections due to filamentous basidiomycetes are extremely rare. We encountered a case of epidural abscess due to Schizophyllum commune that extended from sinusitis. A 53-year-old Japanese man presented at our hospital with a headache. Computed tomography (CT) of the cranium and sinuses showed ethmoid and sphenoid sinusitis with no intracranial abnormalities. The patient was diagnosed with acute sinusitis and underwent antibiotic treatment. However, the symptoms deteriorated, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The rate of human infections caused by S. commune has been increasing recently [3]. Several cases have been reported in immunocompromised and immunocompetent patients [4][5][6][7][8][9][10][11][12][13][14][15][16]. We reviewed published reports of S. commune-induced invasive infections in immunocompetent patients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of human infections caused by S. commune has been increasing recently [3]. Several cases have been reported in immunocompromised and immunocompetent patients [4][5][6][7][8][9][10][11][12][13][14][15][16]. We reviewed published reports of S. commune-induced invasive infections in immunocompetent patients (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed published reports of S. commune-induced invasive infections in immunocompetent patients (Table 1). Even in immunocompetent patients, S. commune induced serious in ammation such as pneumonia or epidural abscess [4,5]. For example, in the US, an immunocompetent 58-year-old man died of pneumonia and brain abscess caused by S. commune [4].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier literature reported that aerobic Gram-negative bacteria accounted for less than 10% of isolates, while in Hlavin et al's report, the aerobic Gram-negative bacteria were cultured in 52% of patients ( 7 ). There have also been reports of fungal cultures in the literature ( 15 , 16 ), and mixed bacterial infections are common as well. Among our 5 patients, 3 cases had positive bacterial cultures, with 1 case for Pseudomonas aeruginosa and 2 cases for Staphylococci .…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed global literatures to identify clinical presentation, underling disease of patients, and treatment for invasive human diseases caused by S. commune , and categorized those cases according to the underlying conditions of host ( Table 2 ) [ 4 5 6 7 8 9 10 15 16 17 18 19 20 ]. We excluded non-invasive cases such as sinusitis without evidence of mucosal invasion in immunocompetent host.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded non-invasive cases such as sinusitis without evidence of mucosal invasion in immunocompetent host. There were four cases of S. commune invasive infection developed in immunocompetent host which were characterize to involve sino-orbital structure or brain [ 8 16 17 18 ]. Although the four patients were classified as immunocompetent, one was an air conditioning installer which might be a risk of fungal infection by route of inhalation.…”
Section: Discussionmentioning
confidence: 99%